Effect of maturity on chlorophyll, tannin, color, and polyphenol oxidase (PPO) activity of sugarcane juice (Saccharum officinarum var. yellow cane) - M. Qudsieh, Hanan Yassin; Yusof, Salmah; Osman, Azizah; Abdul Rahman, Russly (American Chemical Society, 2002)
A study was conducted to determine the effect of sugarcane maturation on the contents of chlorophyll, tannin, and polyphenol oxidase (PPO) activity and on color change of sugarcane juice. The maturation period of the cane studied was between 3 and 10 months after planting. Different parts of the cane, namely, the top, middle, and bottom portions, were analyzed. Results obtained indicated that there were significant (P < 0.01) decreases in total chlorophyll a and b and tannin contents during maturity followed by slower rates of decrease of both parameters at the end of maturity stages. There were no significant differences (P > 0.05) in chlorophyll and tannin contents between the middle and bottom portions. On the other hand, the top portion of the stem had a significantly (P < 0.01) lower concentration of chlorophyll and a significantly (P < 0.01) higher content of tannin. PPO activity of sugarcane juice was determined using chlorogenic acid as a substrate. There was a highly significant difference (P < 0.01) in PPO activity of cane juice during maturity. PPO activity was high at the early development stage, decreased during maturation, and then remained relatively constant at the end of maturity. PPO activity was higher when chlorogenic acid was used as substrate. There were also significant differences (P < 0.01) in juice color (L*, a*, b* values) from different portions at different maturity stages. At the early stages, the color of extracted juice was dark, and then the juice turned to yellowish green during maturity. The decrease in green color or the increase in the yellow color could be associated with the decline in chlorophyll. The overall color change (ΔE) at maturity indicated that the color of the middle and bottom portions was lower than that of the top portion.